Genetic analysis of new 16S rRNA mutations conferring aminoglycoside resistance in Mycobacterium abscessus - Nessar, Rachid (Oxford University Press, 2011)
OBJECTIVES: We studied the development and fitness cost of 2-deoxystreptamine aminoglycoside resistance of Mycobacterium abscessus. METHODS: Spontaneous 2-deoxystreptamine aminoglycoside-resistant mutants were selected and the frequency of their appearance was determined. The 3′ part of the rrs gene was sequenced to characterize mutations. Additionally, we determined the MICs of aminoglycoside drugs for the different mutants obtained. The dominance/recessivity traits of the different mutations were examined and we explored the potential cost conferred by the mutations selected in vitro on the fitness of these isolates compared with the wild-type strain. RESULTS: The in vitro mutation rate for 2-deoxystreptamine aminoglycoside resistance was ∼10(−7) mutations/cell division. In addition to the known rrs A→G substitution at position 1408 (Escherichia coli numbering), which confers kanamycin resistance (Kan(R)), three new substitutions in rrs were identified in M. abscessus Kan(R) mutants, i.e. T→A at 1406, C→T at 1409 and G→T at 1491. Heterodiploids carrying genomic mutations T→A at 1406 and A→G at 1408 with the wild-type rrs gene carried by the pNBV1 vector showed a resistant phenotype. In contrast, heterodiploids carrying genomic mutations C→T at 1409 and G→T at 1491 with the wild-type rrs gene carried by the pNBV1 vector had a susceptible phenotype. No burden on fitness was observed for the different mutations. CONCLUSION: Mutations in the rrs gene that confer high-level 2-deoxystreptamine aminoglycoside resistance on M. abscessus differ in their dominance/recessivity traits and have no biological cost under our experimental conditions.